Pemanfaatan Pati Sebagai Bahan Pembantu Utama Dalam Pembuatan Formulasi Pestisida Controlled Release - Sri Pudji Rahayu; Rofienda Rofienda; Robiatun Robiatun (Balai Besar Kimia dan Kemasan, 1997)
Controlled Rerelease Formulation is one type of Pesticide formulation which can release active ingredient slowly and continuesly in certain period of time. Release on using of there kinds of starch that are corn, cassasa and rice starch was carried autin BBIK laboratory. Xanthate and Board acid methode were used in this formulation making to entrop pesticide active ingredient such as diazinon, carbo:furan and chlorpyrifos into a matrix polimer. From the test of physico-chemical and active ingredient release rate, it was found that com starch can be used well in making of controlled release pesticide formulation while rice starch can not be used for this formulation.